Direct Synthesis of An Aluminosilicate POS Zeolite with Intersecting 12×11×11‐Member‐Ring Pore Channels by Using a Designed Organic Structure‐Directing Agent. Issue 35 (12th May 2022) - Cai, Xianshu; Zhao, Yue; Zhang, Jun; Zi, Wenwen; Tao, Shuo; Jiao, Feng; Du, Hongbin
Abstract: Large and extra‐large pore zeolites have been widely applied in industrial areas as catalysts, adsorbents, etc. Among them, silica and/or aluminosilicate zeolites have been attracted great attention due to their excellent hydrothermal stability and strong acidity. However, a great deal of zeolite structures are still not available in the form of silica and/or aluminosilicate. Herein, we report the synthesis of pure silica and aluminosilicate large‐pore zeolites, denoted as NUD‐14 and Al‐NUD‐14, respectively, by using a designed cation 1‐ethyl‐4‐phenylpyridinium as an organic structure‐directing agent (OSDA). NUD‐14 has an intersecting 12×11×11‐member ring pore system, which is isostructural to the germanosilicate PUK‐16 zeolite with a POS topology. The OSDAs can be completely removed from the framework by calcination. NUD‐14 and Al‐NUD‐14 possess excellent acid and hydrothermal stabilities, superior to the germanosilicate POS zeolite. The incorporation of Al into the zeolite framework makes the Al‐NUD‐14 zeolite possess medium and strong acidities. The successful synthesis of NUD‐14 consisting of a rare odd‐member ring pore structure may provide a platform for interesting size‐ and shape‐selective catalytic applications. Abstract : Pure silica and aluminosilicate zeolites NUD‐14 are directly synthesized by using a designed cation 1‐ethyl‐4‐phenylpyridinium as an organic structure‐directing agent, which show excellent acid and hydrothermal stabilities superior to their counterpart germanosilicate POS zeolite. The incorporation of Al into the zeolite framework makes the Al‐NUD‐14 zeolite possess medium and strong acidities, providing a platform for exploring its size‐ and shape‐selective catalytic applications.